2005
DOI: 10.1007/s00432-005-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Second-line strategies for metastatic renal cell carcinoma: classics and novel approaches

Abstract: Until today, second-line treatment of patients with metastatic RCC progressing under therapy with biological response modifiers remains an unresolved issue. The results of ongoing clinical trials evaluating novel targeted approaches can be expected with suspense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 98 publications
0
23
0
2
Order By: Relevance
“…Consequently, clinical trials as well as guidelines have focused on patients with this RCC subtype. In contrast, patients who suVered from less common tumours such as papillary, chromophobe, sarcomatoid-variant, and collecting-duct tumours have often been excluded or ignored (Schrader et al 2006a). However, genetic and clinical studies during the past two decades have shown that kidney cancer is not a single disease; it consists of a number of diVerent types of cancer that occur in the same organ.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, clinical trials as well as guidelines have focused on patients with this RCC subtype. In contrast, patients who suVered from less common tumours such as papillary, chromophobe, sarcomatoid-variant, and collecting-duct tumours have often been excluded or ignored (Schrader et al 2006a). However, genetic and clinical studies during the past two decades have shown that kidney cancer is not a single disease; it consists of a number of diVerent types of cancer that occur in the same organ.…”
Section: Introductionmentioning
confidence: 96%
“…Renal cell carcinoma (RCC) is a common urologic tumor and accounts for about 3% of all human malignancies (Schrader et al 2006). The annual mortality-to-incidence ratio with RCC is signiWcantly higher compared to other urological malignancies, and its incidence has been increasing steadily in recent decades (Schrader and Hofmann 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although early detection and treatment are considered to be the most effective methods to improve the outcome of patients with any cancer, RCC patients often do not manifest clinical symptoms and receive medical attention until their tumors progress to advanced stages [2][3][4]. Recently, ultrasound and CT scan can detect smaller renal tumors.…”
Section: Introductionmentioning
confidence: 99%